Impact of Macroeconomic Variables on Container Throughput: The Case Study of Sri Lanka - Thalagala, A.M.; Nayanalochana, P.C.J.; Francis, S.J. (Sri Lanka Forum of University Economists, 2025)
Container shipping plays an essential role in international trade, facilitating the efficient, secure, and standardized cargo movements between countries. Container throughput, typically measured ...
Keywords: Container Throughput; Direct Inward and Outward Movements; ARDL Model; Macroeconomic Variables; Time Series Analysis